ANALISIS PERFORMANSI PENDAPATAN OPERASI BERSIH DAN KAPASITAS ANGKUTAN PENUMPANG UDARA RUTE JAKARTA-DENPASAR (STUDI KASUS : PT. GARUDA INDONESIA) - (NIM 28095031), HARDJANA
Abstract : Business competitions that have been taking place in Jakarta-Denpasar flight route were resulted from the fact that there exist a number of airlines serving the route, i.e., Garuda, Merpati Sempati, and Bouraq. In order to retain its market share or, if possible, to increase it, each of the airlines has to improve its . Accordingly, each of them should attempt to identify service variables the customers take into account in choosing product, that is, by identifying preference of users in choosing mode. In the future, any airline needs to predict market share indicated by probabilities of choosing an airline and obtaining income net revenue (INR) through a change from an elastic service variable. By grouping the airlines into two groups (i.e., Garuda, and Non-Garuda), an analysis was performed to obtain the probabilities of choosing Garuda, by using Logit Binary Model, with a parameterizing process by support of SPSS for Windows Release 6.0 program package. Whereas in order to calculate the income, INR was used with Excel Program. From the parameterizing it was obtained the service variables that formed a probability model of choosing moth to be X2 (flight schedule conformity), X7 (sound, tremble/shake), X8 (seat allowance), X9 (room temperature),X 10 (pre-flight service), X11, (in-flight service), X13 (the ease of obtaining tickets), variables. Because from an elasticity analysis there was no elastic sevice variable that the probability of choosing Garuda was constant (unchanged), i.e. 0.6875 (on assumption that the value of each variables was the average value of the respondents\' answers). On assumption that the amount of passangers that departure from Jakarta todays is similiar to that for 1996, it can be obtained some alternative airlines in relation to flight frequency a day that yields revenue, maximum INR is B-737 aircraft type, with 10 (tens) frequence per days and INR = Rp. 105.861.000,-. The rangking is A-300, DC-10, B-747, and MD-11 aircraft type.